CAPACITY BUILDING INITIATIVES FOR SELF-HELP GROUPS (SHGS): AN EVALUATION OF RAJEEVIKA’S INTERVENTIONS - Verma, Khushboo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research article assesses the capability enhancement programmes that Rajeevika, under the Rajasthan Rural Livelihoods Project (RRLP), has implemented to enhance the SHGs. These schemes shall assist to increase women’s banking facilities along with skill building and socio-economic improvement. In this study, both quantitative and qualitative research findings explain the effectiveness of the said interventions on SHG performance, member’s capacity and the general improvement of the community. The results depict the increased levels of understanding in money affairs, employment opportunities, and weak areas in choice making but are faced with resource constraints and cultural barriers.